2002
DOI: 10.1046/j.1524-4725.2002.02099.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Facial Lipoatrophy

Abstract: Lipodystrophy and lipoatrophy are intimately related to infection with HIV. In consequence, facial lipoatrophy is a major stigma for HIV-infected individuals and can have dramatic effects on their self-esteem and socialization. Effective treatment is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 62 publications
1
79
0
1
Order By: Relevance
“…However, if these reference points are also displaced in the same direction as the central circle of measurement, the process of superimposition of scans will in effect minimize the estimated central surface volume difference. Although changes occurring in HIV lipoatrophy are most obvious in the centre of the cheek, in advanced cases they can extend as far as the temples and orbit [14,26]. This source of error was not present in our mannequin model because the plasticine was only applied in the centre of the cheek, and the reference points on the surrounding areas were not affected [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, if these reference points are also displaced in the same direction as the central circle of measurement, the process of superimposition of scans will in effect minimize the estimated central surface volume difference. Although changes occurring in HIV lipoatrophy are most obvious in the centre of the cheek, in advanced cases they can extend as far as the temples and orbit [14,26]. This source of error was not present in our mannequin model because the plasticine was only applied in the centre of the cheek, and the reference points on the surrounding areas were not affected [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with facial changes are more worried about stigmatization. Facial lipoatrophy was cited as an important stigmatizing factor for HIV patients, rendering them more vulnerable to the identification of seropositivity and consequently leading to decreased self-esteem and socialization (9)(10) .…”
Section: Methodsmentioning
confidence: 99%
“…The "contamination" of body image currently associated with lipodystrophy has been documented; however, the mechanisms underlying the visible disfiguring and stigmatizing morphological changes are still unknown (10,15,17) . In addition, BLANCH and colleagues (9) found that decreased sexual enjoyment and activity were observed after the development of lipodystrophy; however, there were no change in the frequency of condom use.…”
Section: Methodsmentioning
confidence: 99%
“…The catalytic site of HIV-protease, to which PIs bind shares approximately 63% of 12-amino acid sequence homology with a region incorporating a lipid binding domain in the low-density lipoprotein receptor-related protein (LRP) and 58% with a C-terminal region of the cytoplasmic retinoic acid binding protein type 1 (CRABP-1) [15,17], respectively. Under normal circumstances, CRABP-1 binds to intracellular retinoic acid (RA) and accelerates its conversion to 9-cis-RA, a major ligand of the retinoic X receptor (RXR) [15,17,25,26]. Then, the heterodimerization of RXR with peroxisome proliferator-activated receptor-gamma (PPAR-γ) significantly enhances the binding affinity of 9-cis-RA to RXR [15,17,25].…”
Section: Pis and Lipid Metabolismmentioning
confidence: 99%
“…This is sabotaged by PIs which increase apoptosis and reduce differentiation of peripheral adipocytes [15,17,25]. PIs have further been reported to inhibit cytochrome P450 3A, which is required for the conversion of RA to cis-9-RA hence contributing to the impairment of peripheral adipocytes functions [17,26,27] and also reduces the expression of PPAR-γ, leading to less differentiation of pre-adipocytes [25].…”
Section: Pis and Lipid Metabolismmentioning
confidence: 99%